Teaching Literacy: A Puzzle-Based Approach - Johannah D Baugher Dr.; Robyn Akins (The Advocate, 2020)
In an effort to achieve stronger, curricular alignment and establish a more concrete relationship between literacy theory and instructional practice, curricular redesign within an undergraduate, literacy methods course commenced. With a clear rationale for why course redesign was necessary, a collective vision rooted with intention and focused on student learning drove the redesign process. After much thought and critical reflection, instructional planning was complete and the Model of the Complete, Literate Student was born. This research-based model holistically identifies ten puzzle pieces critical to one’s literacy development and ultimately, became the framework that anchored all course content. Course redesign was successful and yielded many benefits including: a meaningful showcase of literacy instruction and assessment; improved scaffolding to better support student learning; intentional, instructional planning; richer learning experiences for students; and, opportunities for professional collaboration. While course redesign is complete, the appropriate next step would be to closely examine students’ perceptions of the redesigned course, as well as the effectiveness of the model to further support student learning.